nab-Paclitaxel/carboplatin in elderly patients with advanced squamous non-small cell lung cancer: a retrospective analysis of a Phase III trial - Gridelli C; Chen T; Ko A; O'Brien ME; Ong TJ; Socinski MA; Postmus PE (Dove Medical Press, 2018)
Cesare Gridelli,1 Tianlei Chen,2 Amy Ko,2 Mary E O’Brien,3 Teng Jin Ong,4 Mark A Socinski,5 Pieter E Postmus6 1Division of Medical Oncology, S. G. Moscati Hospital, Avellino, Italy; 2Biostatistics, Celgene Corporation, Summit, NJ, USA; 3Medical Oncology, Royal Marsden Hospital, London, UK; 4Medical Affairs, Celgene Corporation, Summit, NJ, USA; 5Lung Cancer & Esophageal Cancer, Florida Hospital Cancer Institute, Orlando, FL, USA; 6Pulmonary Diseases, Clatterbridge Cancer Center, Liverpool, UK Background: Limited data on elderly patients with squamous advanced non-small cell lung cancer (NSCLC) preclude optimal treatment. Here, we report the outcomes of a retrospective analysis of a subset of patients ≥70 years with squamous histology from the Phase III trial that evaluated nab-paclitaxel/carboplatin vs paclitaxel/carboplatin. Patients and methods: Patients with stage IIIB/IV NSCLC received (1:1) nab-paclitaxel 100 mg/m2 on days 1, 8, and 15 or paclitaxel 200 mg/m2 on day 1, both with carboplatin area under the curve 6 mg×min/mL on day 1 every 3 weeks. The primary endpoint was independently assessed overall response rate as per the Response Evaluation Criteria in Solid Tumors v1.0. Secondary endpoints included progression-free survival, overall survival, and safety. Results: Sixty-five patients ≥70 years with squamous histology were included (nab-paclitaxel/carboplatin, n=35; paclitaxel/carboplatin, n=30). nab-Paclitaxel/carboplatin vs paclitaxel/carboplatin, respectively, resulted in an overall response rate of 46% vs 20% (response rate ratio, 2.29, P=0.029) and a median overall survival of 16.9 vs 8.6 months (hazard ratio, 0.50, P=0.018). No difference was observed in median progression-free survival (5.7 months for both). Incidences of grade 3/4 neutropenia (50% vs 63%), leukopenia (29% vs 37%), fatigue (3% vs 13%), and peripheral neuropathy (3% vs 13%) were lower, but those of thrombocytopenia (21% vs 10%) and anemia (21% vs 7%) were higher with nab-paclitaxel/carboplatin vs paclitaxel/carboplatin. Conclusion: nab-Paclitaxel/carboplatin was efficacious and tolerable in patients ≥70 years with squamous NSCLC. These results build upon prior analyses, indicating that nab-paclitaxel/carboplatin is effective for this difficult-to-treat patient subgroup. Keywords: taxanes, comorbidities, age, chemotherapy, histology